2018
DOI: 10.1096/fj.201800001rr
|View full text |Cite|
|
Sign up to set email alerts
|

APR3 modulates oxidative stress and mitochondrial function in ARPE‐19 cells

Abstract: Impairment of retinal pigment epithelial (RPE) cells is considered a key contributor to the development of age-related macular degeneration. Apoptosis-related protein 3 (APR3) was recently discovered after treatment with all- trans retinoic acid, a pivotal molecule in RPE cells. However, the function of APR3 remains poorly understood. In the present study, we found that APR3 could interact with nuclear factor (erythroid-derived 2)-like 2, which is a regulator of phase II enzymes, and that knockdown of APR3 pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 44 publications
(50 reference statements)
0
4
0
Order By: Relevance
“…The ARPE-19 human RPE cell line was purchased from the American Type Culture Collection (Manassas, VA, USA). ARPE-19 cells are an accepted cell model for the study of oxidative stress and anti-oxidants effects on RPE cells [23,24,25,26]. Cells were cultured in DMEM/F-12 (1:1) supplemented with 10% heat-inactivated Fetal Calf Serum, 2 mM l -Glutamine, 100 U/ml Penicillin, 100 μg/mL Streptomycin and 50 μg/mL Neomycin and passages 3 to 7 were used.…”
Section: Methodsmentioning
confidence: 99%
“…The ARPE-19 human RPE cell line was purchased from the American Type Culture Collection (Manassas, VA, USA). ARPE-19 cells are an accepted cell model for the study of oxidative stress and anti-oxidants effects on RPE cells [23,24,25,26]. Cells were cultured in DMEM/F-12 (1:1) supplemented with 10% heat-inactivated Fetal Calf Serum, 2 mM l -Glutamine, 100 U/ml Penicillin, 100 μg/mL Streptomycin and 50 μg/mL Neomycin and passages 3 to 7 were used.…”
Section: Methodsmentioning
confidence: 99%
“…Shortly thereafter, it was recognized in a cDNA library derived from CD34+ hematopoietic stem/progenitor cells (HSPCs) and named HSPC013 [ 22 ]. Various isoforms of ATRAID have been used in previous studies, most often Iso B [ 5 , 6 , 7 , 8 , 10 , 23 , 24 ]. In NCBI, three RefSeq transcripts of ATRAID can be found, NM_016085 (Iso A), NM_080592 (Iso B), and NM_001170795 (Iso C).…”
Section: Discussionmentioning
confidence: 99%
“…In transfection experiments with N‐terminal‐tagged ATRAID Iso B, Li and coworkers observed that ATRAID interacted with NRF2 and KEAP1 in the mitochondria of ARPE‐19 cells [ 10 ]. In transduced cell lines expressing C‐terminal Myc‐Flag‐tagged ATRAID Iso C, we did not observe any colocalization between ATRAID and the mitochondrial protein TOMM20 (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation